Fortalezas internas y externas de adolescentes que no consumen alcohol - Mydori Harumi Téllez Vásquez; Carlos Omar Sánchez-Xicoténcatl; Patricia Andrade Palos (Centros de Integración Juvenil A.C., 2017)
Introduction: alcohol consumption in Mexican adolescents is a public health problem, so research efforts should focus on prevention. This study is based on Benson's model of assets (2007), which mention that young people have individual and contextual resources that promote positive development and limit their involvement in risk behavior. Objective: to analyze differences in internal and external assets in high school students with different levels of alcohol consumption. Method: participants were 990 students from public secondary schools in Mexico City, 52.1% female and 47.9% male, the mean age of participants was 13.6 years. Seven internal and seven external assets were evaluated. Results: 53.9% of the participants never consumed alcohol, 28.3% had consumed but never or only once they had abused and 17.8% reported abusing consumption in the last month. Men and women who have not consumed alcohol reported significantly higher scores on internal assets. In the case of external assets, young people who have not consumed alcohol also scored significantly higher in all assets, except for healthy friends in both men and women and support and supervision of the father in men. Discussion and conclusions: the results contribute to the explanation of alcohol consumption among young people and provide elements for the design of interventions to emphasize the assets that should be promoted to prevent young people from drinking alcohol at an early age.----------------------- Introducción: el consumo de alcohol en adolescentes mexicanos es un problema de salud pública, que requiere enfocar los esfuerzos de investigación en la prevención. Este estudio se basa en el modelo de fortalezas de Benson (2007), quien plantea que los jóvenes poseen recursos individuales y contextuales que promueven un desarrollo positivo y limitan el involucramiento en conductas de riesgo. Objetivo: analizar las diferencias en fortalezas internas y externas entre estudiantes de secundaria que presentan diferentes niveles de consumo de alcohol. Metodo: participaron 990 estudiantes de secundarias públicas de la Ciudad de México, 52.1% mujeres y 47.9% hombres, de una media de edad de 13.6 años. Se evaluaron siete fortalezas internas y siete externas. Resultados: 53.9% de los participantes nunca ha usado alcohol, 28.3% sí lo ha consumido pero nunca o sólo una vez ha abusado, y 17.8% reportó haber abusado del consumo en el último mes. Hombres y mujeres que no han usado alcohol reportaron puntajes significativamente más altos en fortalezas internas. En el caso de las fortalezas externas, los jóvenes sin consumo fueron los que obtuvieron puntajes más altos, excepto en amigos saludables (tanto hombres como mujeres), y en apoyo y supervisión del padre (hombres). Conclusiones: los resultados contribuyen a la explicación del consumo de alcohol en jóvenes y proporcionan elementos para el diseño de intervenciones, pues señalan las fortalezas que deben promoverse para evitar que los jóvenes consuman alcohol a edades tempranas.